Constitutional, philosophical and historical perspectives of the capital punishment debate in Australia and the United States - Moens, Gabriel; Thompson, A. (George Bacovia University, 2012)
Capital punishment has been abolished in all Australian States. However, public demands for the reintroduction of the death penalty continue to be heard intermittently in Australia, especially after a gruesome murder or other atrocity. A discussion of the appropriateness and desirability (as opposed to the legality or illegality) of the death penalty is never completely removed from the Australian and American political agenda. An objective observer cannot fail to notice that, in general, such discussion is often carried on by people who have preconceived and inflexible views. An inevitable result is the polarisation of the capital punishment debate. In these circumstances, an insistence on cogent reasoning is clearly warranted.